Gawe van die lewende God: Die Nagmaal in trinitariese perspektief - Walt, F. van der (Koers, 1990)
Holy Communion in trinitarian perspective. Christ is truly present in the sacrament of Holy Communion and this presence is a gift of the triune God. Christ’s words of institution clearly point to his self-sacrifice, but his sacrifice must not be isolated from the fact that God the Father also sacrificed his Son for all of us. This sacrifice does not only reveal something about the Son, but also about the Father. In Holy Communion, the gift of the Holy Spirit is our communion with Christ. Scripture however also points to the Spirit's involvement in the sacrifice of Christ. Furthermore the Spirit works in our hearts, activating our surrender as an answer to Christ's self-surrender.